Regenerative and Conventional Intra-Articular Therapies in Osteoarthritis: A Narrative Review with a Focus on Sports Medicine - Rafalska, Izabela; Smagoń, Jakub; Kaim, Martyna; Majewska, Melania; Piasecka, Natalia; Siewiera, Wiktoria; Bober, Joanna; Kornacka, Natalia; Bednarski, Krzysztof; Bochenek, Magdalena (Quality in Sport, 2026)
Background. Osteoarthritis (OA) is one of the leading causes of chronic pain and functional limitation worldwide and represents a significant challenge not only in the general population but also in physically active individuals, where joint integrity is essential for maintaining mobility and performance. Aim. The aim of this study was to present current evidence regarding the efficacy and safety of conventional and modern intra-articular injections in the treatment of osteoarthritis, with particular emphasis on their relevance in sports medicine and physically active populations. Materials and Methods. This study was designed as a structured narrative review synthesizing available data on intra-articular therapies, including glucocorticosteroids, hyaluronic acid, platelet-rich plasma (PRP), collagen, mesenchymal stem cells (MSC), and bone marrow aspirate concentrate (BMAC), as well as injection techniques and combined therapeutic approaches. Results. Available evidence indicates that corticosteroids provide primarily short-term pain relief, whereas hyaluronic acid may offer moderate symptomatic improvement. Platelet-rich plasma demonstrates promising results in terms of longer-term pain reduction and functional improvement, which may be particularly relevant for maintaining physical activity levels. Cell-based therapies and collagen injections represent emerging approaches, although they require further standardization and high-quality clinical trials. Conclusions. Modern intra-articular injections may constitute an important component of integrated osteoarthritis management, particularly in individuals aiming to maintain mobility and physical performance. These therapies may play a key role within personalized treatment strategies in sports medicine and rehabilitation.